FUNGSI KESENIAN TONGKIR PADA PAGUYUBAN SENI TONGKIR SELERA HATI DI DESA NGARINGAN KABUPATEN BLITAR - Dinda Rahayu; Ananto Sabdo Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
The research titled “The Function of Tongkir Art in the Selera Hati Tongkir Art Community in Ngaringan Village” is motivated by the researcher’s interest in the functional aspects of tongkir art, which remains preserved within the community. This art form reflects strong social dynamics, where its social functions emerge through cultural interaction and musical innovation, particularly through the integration of gamelan instruments. Thepurpose of this study is to describe and analyze the functions of tongkir art within the socio-cultural context of thelocal society. The research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The functions of the art are analyzed using Allan P. Merriam’s theoretical framework, which encompasses entertainment, communication, and cultural preservation functions. The results show that tongkir art serves as a means of entertainment, a medium for social and expressive communication, and a tool for thetransmission of cultural values. The Selera Hati Tongkir Art Community plays a key role in maintaining the existence and continuity of tongkir art in Blitar Regency.